KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MODEL RECIPROCAL TEACHING (RT) DAN MODEL AIR AUDITORY INTELLECTUALY REPETITION (AIR) - Susanto, Andi (Math Educa Journal, 2019)
The purpose of this research was to determine the ability to understand the mathematical concepts of students taught by reciprocal teaching models with an intellectually repetition model in SMP N 6 Kota Solok. This type of research is a quasy experiment with a randomized control group only design. Test instruments the ability to understand mathematical concepts. Based on the test result obtained the average ability to understand the mathematical concepts of students by reciprocal teaching model 81,66 by auditory intellectually repetition model 77,75 and ordinary learning 73,91. Hypothesis testing indicated that the ability to understand the mathematical concepts of students by reciprocal teaching model and the auditory intellectually repetition model were higher than the ordinary learning model. Beside it, it was also concluded that there were difference in the ability to understand mathematical concepts with reciprocal teaching model and auditory intellectually repetition model.